COVID-19 vaccine intention among young adults: Comparative results from a cross-sectional study in Canada and France. Issue 16 (6th April 2022) - Coulaud, Pierre-julien; Ablona, Aidan; Bolduc, Naseeb; Fast, Danya; Bertrand, Karine; Ward, Jeremy K.; Greyson, Devon; Jauffret-Roustide, Marie; Knight, Rod
Highlights: We found higher vaccine uncertainty and refusal among youth in France versus Canada. Youth who reported COVID-19 preventive actions had higher levels of vaccine acceptance. Youth living in rural areas and with low levels of education are priority groups for vaccination efforts. Abstract: Background: High rates of COVID-19 vaccination uptake are required to attain community immunity. This study aims to identify factors associated with COVID-19 vaccine uncertainty and refusal among young adults, an underexplored population with regards to vaccine intention generally, in two high-income settings: Canada and France. Methods: A cross-sectional online survey was conducted from October to December 2020 among young adults ages 18–29 years (n = 6663) living in Canada (51.9%) and France (48.1%). Multinomial logistic regression analyses were performed to identify the sociodemographic and COVID-19-related measures (e.g., prevention behavior and perspectives, health-related concerns) associated with vaccine uncertainty and refusal. ﻿We conducted weighted analyses by age, gender and province/region of residence. Results: Intention to accept vaccination was reported by 84.3% and 59.7% of the sample in Canada and France, respectively. Higher levels of vaccine uncertainty and refusal were observed in France compared to Canada (30.1% versus 11%, 10.2% versus 4.7%). In both countries, we found higher levels of vaccine acceptance among young adults who reported COVID-19 prevention actions. Vaccine uncertainty and refusal were associated with living in a rural area, having lower levels of educational attainment, not looking for information about COVID-19, not wearing a face mask, and reporting a lower level of concern for COVID-19′s impact on family. Participants who had been tested for COVID-19 were less likely to intend to refuse a vaccine. Conclusions: COVID-19 vaccine acceptance was high among young adults in Canada and France during a time in which vaccines were approved for use. Targeted interventions to build confidence in demographic groups with greater hesitance (e.g., rural and with less personal experience with COVID-19) may further boost acceptance and improve equity as vaccine efforts continue to unfold.